The levels of epithelial anchor proteins β-catenin and zona occludens-1 are altered by E7 of human papillomaviruses 5 and 8 - Heuser, Sandra; Hufbauer, Martin; Marx, Benjamin; Tok, Ali; Majewski, Slawomir; Pfister, Herbert; Akgül, Baki (Journal of General Virology, 2016)
Infection with viruses of the genus Betapapillomavirus, β-human papillomaviruses (β-HPV), is implicated in the development of non-melanoma skin cancer. This was first evidenced for HPV5 and HPV8 in patients with the skin disease epidermodysplasia verruciformis (EV). The relocalization of the junctional bridging proteins β-catenin and zona occludens-1 (ZO-1) from the adherens and tight junctions are common processes of the epithelial-mesenchymal transition (EMT) associated with tumour invasion. Here, we report that β-catenin and ZO-1 are strongly upregulated by the E7 oncoproteins of HPV5 and HPV8 in keratinocytes grown in organotypic skin cultures. Although the membrane-tethered form of β-catenin was elevated, no signs of β-catenin activity within the canonical Wnt signalling pathway could be detected. The upregulation of β-catenin and ZO-1 could also be confirmed in the skin of HPV8 transgenic mice as well as in cutaneous squamous cell carcinomas of EV patients. These data provide the first evidence that β-catenin and ZO-1 are direct targets of E7 of the oncogenic β-HPV types 5 and 8. The ability to deregulate these epithelial junction proteins may contribute to the oncogenic potential of these viruses in human skin.